Impact of Electric Vehicle Transition Scenarios on Road Transport Emission in Semarang City - Pratiwi, Ningsih Ika; Suherman, Suherman; Yulianto, Bambang; Amin, Muhammad (Universitas Diponegoro, 2025)
The transition from fossil-fueled vehicles into electric vehicles is considered to be a strategy that can significantly reduce emissions and improve urban air quality. This study aims to examine the impact of the battery electric vehicles growth in Semarang City on carbon emissions within the road transport sector. Projections were made to assess the long-term impact and contribution of this trend towards meeting government targets in 2030 and 2060. Low Emission Analysis Platform (LEAP) software was used to estimate carbon emissions based on amount of vehicle and vehicle kilometer traveled (VKT) data. Three scenarios were set: the BEV scenario, which focuses on the widespread use of electric vehicles, demonstrates a significant reduction, especially in PM10 emissions, highlighting the advantages of transitioning away from internal combustion engine vehicles. The EMX scenario, which emphasizes an energy mix plan to support electricity, does not demonstrate a significant reduction in emissions. The COM scenario, which combine the BEV and EMX scenarios achieves the lowest emissions overall, indicating that a comprehensive strategy is most effective for achieving long-term emission reductions. All scenarios indicate the need for more aggressive policies, technological innovations, and carbon capture strategies to achieve reduction targets, particularly in the road transport sector.